Trinidad - (:unkn) unknown (My University, 2009)
A picture of a rural road lined with tall coconut trees.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Coconut palm; Agriculture; Plantations